Does the ethno-religious diversity of a neighbourhood affect the perceived health of its residents? - Russell Jonsson, Kenisha (Social science & medicine, 2018)
Concerns about the diversification of Britain, and its impact on social capital and health are widely debated. The literature has however produced a fuzzy discourse, full of assumptions and claims that are rarely tested. We attempt to disentangle some of these assumptions by providing empirical evidence on the mediating and moderating influence of inter-ethnic conflict and contact, and examine whether they underlie the erosion of health among minorities and white British respondents residing in diverse local areas. Analyses were conducted using multilevel models that relied on geocoded data from a random stratified sample of adults 16-75 years collected in the 2009-2011 Citizenship Survey merged to small area aggregated statistics from the 2011 UK census. The final sample comprised of minorities (n=13,236) and white British (n=15,021) residing in England. We find that local area deprivation matters much more for the health of minorities and whites than diversity. Yet, residing in diverse areas can be problematic for whites if it is accompanied by high levels of social distance measured by negative attitudes towards immigrants. Greater contact among minorities and whites, residing in more diverse areas appears to have no significant effect on health. Overall, the findings supported our hypothesis that residing in areas of greater diversity has a differential impact on minorities when compared to whites. In particular, diversity appear to be more beneficial for minorities, especially newly arriving migrants. The effect of contact as measured by social capital is dwarfed in comparison to the effect of deprivation, underlying the importance for policy makers to tackle structural inequalities.